Dampak Angkutan Sampah Tempat Pembuangan Sampah (TPA) Putri Cempo Terhadap Kinerja Lalu Lintas (Studi Kasus Simpang Jalan Mayor Ahmad - Jalan Pelangi Raya, Surakarta) - Ilonka, Willy Anastasya; Handayani, Dewi (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2022)
Putri Cempo TPA is the largest TPA in Surakarta City. The presence of vehicles transporting waste to and from the Putri Cempo TPA has an impact on the main roads and intersections leading to the Putri Cempo TPA. The results of the research on the existence of waste transportation can reduce roads up to 28.24% even though they are still in decent condition. The performance of the intersection has decreased to 2.98%, and has reached an unfeasible condition.